A microclimate study of FSPU, UiTM Shah Alam / Sabarinah Sh. Ahmad and Norhati Ibrahim - Sh. Ahmad, Sabarinah; Ibrahim, Norhati (2003)
A field study was conducted in classrooms in Malaysia which were either mechanically ventilated by fans or air-conditioned, to assess their thermal conditions during the day. Samples of occupants were asked to answer a survey on their perception of the comfort level while thermal comfort variables were measured simultaneously. Data analysis of the mechanically ventilated classrooms showed that all classrooms had thermal conditions that fell outside the comfort zone of ASHRAE Standard 55. However, the occupants found the warmer thermal conditions acceptable. Meanwhile, half of the air-conditioned classroom had thermal conditions that were within the comfort zone of ASHRAE Standard 55. The other half had thermal conditions that are higher than the ASHRAE comfort zone but the occupants found the thermal conditions acceptable.